Modelling damage mechanisms of concrete under high confinement pressure. (April 2021) - Wang, Yin; Kong, Xiangzhen; Fang, Qin; Chen, Li; Fan, Junyu
Highlights: Three damage mechanisms of concrete subjected to intensively dynamic loadings are identified and physically modelled. The hydrostatic damage and shear damage models can well reproduce the test data demonstrated by numerical single element tests. The competition mechanism of hydrostatic damage and shear damage during a triaxial compression test is well captured. Physical mechanisms of experimentally observed crater, crack, tunnel and spall failures in concrete structures are revealed. Abstract: Dynamic failures (e.g., crater, crack and spall) can be observed in concrete structures when suffered from possible blast and impact loadings. Understanding the physical mechanisms behind these failures needs a sound material model that thoroughly considers the damage mechanisms of concrete material, especially under the high confinement situation existed near the projectile and explosion. Modelling the damage mechanisms is a challenging problem that is not fully resolved in the commonly-used concrete material models. In this study, three kinds of damage mechanisms of concrete material, i.e., the hydrostatic damage due to pore collapse, shear damage due to shear-induced microcracking and tensile damage due to tensile microcracking are identified and physically modelled respectively using corresponding damage indexes. The interaction of the three damage is also considered by introducing two stress-dependent factors. The damage model is implemented into the Kong-Fang material model recently proposed, in which improvements on the strength surfaces, strain-rate enhancement and erosion criterion are accompanied made based on a few years use of this model. Numerical triaxial compression test and hydrostatic compression to unconfined compression test are conducted using a single element to validate the proposed hydrostatic damage model and the shear damage model. And the competition mechanism between hydrostatic damage and shear damage during the triaxial compression test is discussed. Then the modified Kong-Fang model is used to numerically simulate the reinforced concrete slabs subjected to a contact explosion load and projectile impact load, in which the physical mechanisms of the experimentally observed crater, crack, tunnel and spall failures are revealed.